Development of a Functional Digital Integrated Circuit Testing System Using Mixed-Mode Technique - Md. Abubaker Sheikh, Md. Liakot Ali (2004)
With the continuous increase in design complexities and packing densities of integrated circuit (IC), problems associated with conventional Automatic Test Equipment (ATE)-based IC testing approach have become a burning issue in the semiconductor world, which needs an economic solution with reliable performance. Recently, the superiority of Dynamic Reseeding-based Mixed-mode (DRM) technique has been proven over all other existing test techniques in the Built-in Self-Test (BIST) environment. This thesis introduces the implementation of the DRM technique in a system-on-a-chip (SOC) in alleviating the problems of conventional ATE-based external testing of digital IC. The performance of the SOC in IC testing has been verified using fault simulation experiments on the ISCAS85 benchmark circuits (Circuits proposed in the International Symposium on Circuits and Systems in 1985). Significant improvement is observed in achieving complete fault coverage for the ISCAS85 benchmark circuits using acceptable number of test vectors. Fault simulation results show that the proposed DRM technique produces 100% fault coverage for the benchmark circuits c432, c1355, c1908, c2670, c3540 and c5315 using the 232, 526, 996, 336, 360 and 748 test cubes, respectively which are much lower than the numbers from the approaches suggested by other researchers. It also offers much lower data storage requirements in IC testing than the conventional ATE-based testing approach. The results show that 2 to 11 times less memory is needed for testing the ISCAS85 benchmark circuits using the DRM technique than that of the deterministic testing approach.